Configuring Symantec AntiVirus corporate edition - Hunter, Laura E.; Shimonski, Robert (Rockland, Mass. : Syngress, 2003)
This is the only book that will teach system administrators how to configure, deploy, and troubleshoot Symantec Enterprise Edition in an enterprise network. The book will reflect Symantec's philosophy of "Centralized Antivirus Management." For the same reasons that Symantec bundled together these previously separate products, the book will provide system administrators with a holistic approach to defending their networks from malicious viruses. This book will also serve as a Study Guide for those pursuing Symantec Product Specialist Certifications. Configuring Symantec AntiVirus Enterprise Edition contains step-by-step instructions on how to Design, implement and leverage the Symantec Suite of products in the enterprise. ΆFirst book published on market leading product and fast-growing certification. Despite the popularity of Symantec's products and Symantec Product Specialist certifications, there are no other books published or announced. ΆLess expensive substitute for costly on-sight training. Symantec offers week-long courses on this same product for approximately $2,500. This book covers essentially the same content at a fraction of the price, and will be an attractive alternative for network engineers and administrators. ΆFree practice exam from solutions@syngress.com. Syngress will offer a free Symantec Product Specialist Certification practice exam from syngress.com. Comparable exams are priced from $39.95 to $59.95.
1: Introduction -- 2: Centralized AntiVirus Management -- 3: Classifying Malicious Viruses -- 4: Configuring Norton AntiVirus 2.5 for Gateways -- 5: Configuring Norton AntiVirus 2.5 for Microsoft® Exchange -- 6: Configuring Norton AntiVirus 2.5 for Lotus Notes / Domino -- 7: Configuring Norton AntiVirus Corporate Edition 7.6 -- 8: Configuring Symantec Web Security 2.0 -- 9: Troubleshooting Symantec AntiVirus Enterprise Edition -- 10: Testing your Deployment -- 11: Securing Workstations -- 12: Updating Your Virus Definitions -- 13: Backup and Disaster Recovery -- 14: Preparing for Symantec Product Specialist Certification -- 15: Conclusion.
Includes index.
Keywords: Computer viruses; Computer networks -- Security measures; Electronic books